The impact of applying knowledge management on institutional performance, an applied study on the Social Security Fund in the city of Benghazi (Economic studies journal, 2020)
The study aimed to identify the impact of the application of knowledge management and its dimensions (knowledge acquisition, documenting knowledge, knowledge transfer, application of knowledge) on the institutional performance in the Social Security Fund in Benghazi. To achieve the objectives of the study, the researchers followed the descriptive and analytical method, and used the questionnaire form as the main tool in data collection. The study population consisted of all 110 senior, middle and executive directors. Through their full study, the researchers used a comprehensive inventory method, and the statistical packages for Social Sciences (SPSS) in the data analysis process. The study reached many results, the most important of which are: The level of knowledge management and the degree of institutional performance has been high. As well as the presence of a statistically significant impact of knowledge management with its combined dimensions on the institutional performance. In addition, there is a statistically significant impact of each dimension of knowledge management (knowledge acquisition, documenting knowledge, knowledge transfer, application of knowledge) on organizational performance. The study presented a set of recommendations that contribute to enhancing the role of knowledge management in improving the institutional performance of the Social Security Fund in Benghazi
Keywords: : Knowledge Management; Institutional Performance; Social Security Fund in Benghazi Libya